Analysis of Risk Factors for Non-union After Surgery for Limb Fractures: A Case-Control Study of 669 Subjects - Quan, Kun; Xu, Qiang; Zhu, Meisong; Liu, Xuqiang; Dai, Min (Frontiers in Surgery, 2021)
Objective: The purpose of this study was to analyse the risk factors for limb fracture non-union in order to improve non-union prevention and early detection. Methods: A total of 223 patients with non-union after surgery for limb fractures performed at our institution from January 2005 to June 2017 were included as the case group, while a computer-generated random list was created to select 446 patients with successful bone healing after surgery for limb fractures who were treated during the same period as the control group, thus achieving a ratio of 1:2. The medical records of these patients were reviewed retrospectively. Age, sex, body mass index, obesity, smoking, alcohol, diabetes, hypertension, osteoporosis, fracture type, multiple fractures, non-steroidal anti-inflammatory drugs (NSAIDs) use, delayed weight bearing, internal fixation failure, and infection data were analysed and compared between the two groups. A multivariate logistic regression model was constructed to determine relevant factors associated with non-union. Results: After comparison between two groups by univariate analysis and multivariate logistic regression, we found some risk factors associated that osteoporosis (odds ratio [OR]=3.16, 95% confidence interval [CI]: 2.05-4.89, p<0.001), open fracture (OR=2.71, 95%CI: 1.72-4.27, p<0.001), NSAIDs use (OR =2.04, 95%CI:1.24-3.37, p=0.005), delayed weight bearing (OR=1.72, 95%CI: 1.08-2.74, p=0.023), failed internal fixation (OR=5.93, 95%CI: 2.85-12.36, p<0.001), and infection (OR=6.77, 95%CI: 2.92-15.69, p<0.001) were independent risk factors for non-union after surgery for limb fractures. Conclusions: Osteoporosis, open fracture type, NSAIDs use, delayed weight bearing, failed internal fixation, and infection were found to be the main causes of bone non-union; clinicians should, therefore, take targeted measures to intervene in high-risk groups early.